PENERAPAN STRATEGI PERSONAL SELLING PADA PERUSAHAAN ALDINA BAKERY KOTA TASIKMALAYA - Iis Miati (Pascasarjana Universitas Halu Oleo, 2021)
The development of the bakery business in Indonesia can now be fairly rapid. The existence of bread that is starting to be liked by all circles of society makes this bakery business a promising business. The scale of business in this field is also diverse, ranging from small, medium to large industries.The purpose of this study was to determine the application of personal selling strategies at Aldina Bakery Tasikmalaya.Personal Selling is one way to market products to increase company revenue. The increase in a company will be a support for the existence of a business to remain standing in the midst of competition with other companies, both those that have been around for a long time and with emerging competitors.The method used in this research is descriptive research method with a qualitative approach.The results obtained are that the Aldina bakery company has implemented the stages of personal selling, which have not been implemented optimally, namely: Pre-approach, Overcoming Objections and Follow-up and Maintenance. While those that have been implemented optimally are looking for prospective customers and qualifying them, presentations and demonstrations and closing salesIn addition, Aldina bakery also applies a form of personal selling including Door to door selling, Mail order, Telephone selling, Direct selling.